Neuronal CRMP2 phosphorylation inhibition by the flavonoid, naringenin, contributes to the reversal of spinal sensitization and arthritic pain improvement - Yue-Peng Jiang; Song Wang; Wei-Dong Lai; Xue-Qing Wu; Yan Jin; Zheng-Hao Xu; Aubin Moutal; Rajesh Khanna; Ki Duk Park; Zhi-Ming Shan; Cheng-Ping Wen; Jie Yu (Arthritis Research & Therapy, 2022)
Abstract Background Rheumatoid arthritis patients usually suffer from arthritic chronic pain. However, due to an incomplete understanding of the mechanisms underlying autoimmune disorders, the management of arthritic pain is unsatisfactory. Here, we investigated the analgesic effect and underlying mechanism of the natural flavonoid naringenin (NAR) in collagen-induced arthritis (CIA) pain. Methods NAR was injected (i.p.) once per day for 42 days after initial immunization, and rats were sacrificed on the 28th (the 21st day after final immunization, PID 21) and 42nd days (PID 35). The inflammatory factors, central sensitization indicators, and CRMP2 phosphorylation, as well as the anti-rheumatoid activity and analgesic effect of NAR, were further investigated. Results We found that NAR decreased the arthritis score and paw swelling, as well as the mechanical and thermal pain. The immunofluorescence results also showed a dose dependent effect of NAR on reducing the expressions of spinal cFos, IBA-1, and GFAP on the 28th (PID 21) and 42nd day (PID 35). NAR decreased the phosphorylation of CRMP2 S522 and the expression of the kinase CDK5 in the spinal dorsal horn, but pCRMP2 Y479 was unchanged. In addition, CRMP2 was co-localized with NEUN, but not IBA-1 or GFAP, indicating the involvement of neural CRMP2 phosphorylation in CIA-related pain. Finally, CRMP2 S522 phosphorylation selective inhibitor (S)-lacosamide also alleviated arthritic pain. Conclusions Taken together, our results demonstrate that NAR alleviates inflammation and chronic pain in CIA model, which might be related to its inhibition of neuronal CRMP2 S522 phosphorylation, potentially mitigating the central sensitization. Our study provide evidence for the potential use of NAR as non-opioid-dependent analgesia in arthritic pain.